Pengaruh Rasio Likuiditas, Rasio Leverage Dan Rasio Aktivitas Terhadap Return Saham (Studi Kasus Pada Perusahaan Food and Beverage yang Terdaftar di BEI Periode2017-2019). - Cindy Pragati Pratiwi; Agus Widarko; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this study was to determine the effect of liquidity ratios, leverage ratios, and activity ratios on stock returns. The population in this study were all food and beverage companies listed on the Indonesia Stock Exchange in 2017-2019. The research sample used purposive sampling technique. From a population of 24 companies, a sample of 18 companies was taken with a three-year research period (2017-2019). The data analysis technique used is multiple linear regression analysis. Based on the results of the study indicate that liquidity (Current Ratio) and Leverage (Debt to Equity Ratio) have a negative and insignificant effect on stock returns. Meanwhile, Activity (Total Assets Turn Over) has a positive and insignificant effect on stock returns.. Keywords: CR, DER, TATO, and Stock Returns